Assessing genetic diversity of Maize (Zea mays L.) genotypes for agronomic traits (Research in Agriculture Livestock and Fisheries, 2015)
Maize is one of the most important cereals globally and a promising cereal supplement in Bangladesh. The current study was undertaken to assess genetic diversity among nine maize genotypes. Data were recorded on seven morphological traits viz. plant height (cm), ear height (cm), ear length (cm), ear diameter (cm), number of kernels/ear, 1000-kernel weight (g) and yield/plant (g). Statistical analysis showed significant variation among maize genotypes. Considering plant height, ear length, ear diameter, ear height, number of kernels/ear and yield/plant BHM-7 was observed as the best one. Among all the traits higher phenotypic coefficient of variation and genotypic coefficient of variation were observed for yield/plant. Genetic advance was highest for 1000-kernel weight followed by number of kernels/ear. The correlation study revealed only two positive significant associations: plant height with yield/plant and ear diameter with ear length. Nine genotypes were grouped into three clusters. These all clearly indicated the presence of ample genetic diversity among maize genotypes which can be exploited in future breeding program for better utilization of maize germplasm.Res. Agric., Livest. Fish.2(1): 53-61, April 2015